2017
DOI: 10.3390/s18010031
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy Analysis of Capacitance Data of a Coplanar Electrode Array for Fast and Stable Imaging Processing

Abstract: A coplanar electrode array sensor is established for the imaging of composite-material adhesive-layer defect detection. The sensor is based on the capacitive edge effect, which leads to capacitance data being considerably weak and susceptible to environmental noise. The inverse problem of coplanar array electrical capacitance tomography (C-ECT) is ill-conditioning, in which a small error of capacitance data can seriously affect the quality of reconstructed images. In order to achieve a stable image reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…An efficient method for analyzing metabolic pathways is to integrate the metabolome and transcriptome ( Zhao et al., 2021 ). RDA has proven to be an effective technique for identifying important factors in metabolite biosynthesis ( Wen et al., 2017 ; Hu et al., 2022 ). In our study, L-lysine, L-ornithine, and L-arginine were expressed in accordance with their corresponding structural genes ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…An efficient method for analyzing metabolic pathways is to integrate the metabolome and transcriptome ( Zhao et al., 2021 ). RDA has proven to be an effective technique for identifying important factors in metabolite biosynthesis ( Wen et al., 2017 ; Hu et al., 2022 ). In our study, L-lysine, L-ornithine, and L-arginine were expressed in accordance with their corresponding structural genes ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The planar ECT sensor has electrodes distributed uniformly on an electrode plane and uses the fringing electric field for detection of objects. A lot of effort has been put into the research of planar ECT sensor for applications such as landmine scanning (Tholin-Chittenden and Soleimani, 2017; Tholin-Chittenden et al , 2018), surface or subsurface defect detection (Wen et al , 2017; Pan et al , 2021; Suo et al , 2021; Zhang et al , 2021) and obstacle and pressure sensing in robotics (Ma and Soleimani, 2020). Although the single-plane planar ECT sensor is reported to successfully reconstruct 2D or 3D images and locate the position of defects correctly, it has limitation in terms of the height sensing and depth detection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this paper investigates a dual-plane miniature planar 3D ECT sensor using nine distributed electrodes arranged in 3 × 3 matrix electrode array in each electrode plane. The proposed 3 × 3 matrix electrode array optimises the electrode pairs to neighbouring and opposing electrode pairs only, as these electrode pairs contribute the most to image reconstruction (Wen et al , 2017). The sensitivity distribution of dual-plane on-chip 3D ECT sensor was analysed and compared to the single-plane miniature planar 3D ECT sensor for studying its feasibility in improving the height of 3D reconstructed image.…”
Section: Introductionmentioning
confidence: 99%
“…Ong et al reported a method of using capacitance to monitor water content in civil engineering materials [21]. Particularly, by using a multielectrode sensor, electrical capacitance tomography (ECT) is imaging and visualizing dielectric changes of multiphase or multicomponent processes with different permittivities [22,23,24,25,26,27,28,29,30,31]. The core of ECT is to arrange a number of electrodes around the object and measure the variations of capacitances between different electrode pairs, and then generate its cross-sectional image by using certain reconstruction algorithms.…”
Section: Introductionmentioning
confidence: 99%